Advance care planning in motor neuron disease: A qualitative study of caregiver perspectives. (May 2016) - Murray, Leigh; Butow, Phyllis N; White, Kate; Kiernan, Matthew C; D'Abrew, Natalie; Herz, Helen
Background: Motor neuron disease is a fatal disease, characterised by progressive loss of motor function, often associated with cognitive deterioration and, in some, the development of frontotemporal dementia. Life-sustaining technologies are available (e.g. non-invasive ventilation and enteral nutrition) but may compromise quality of life for some patients. Timely commencement of 'Advance Care Planning' enables patients to participate in future care choices; however, this approach has rarely been explored in motor neuron disease. Aim: We aimed to investigate caregiver perspectives on the acceptability and impact of advance care planning, documented in a letter format, for patients with motor neuron disease and caregivers. Design: This is a qualitative cross-sectional study. Data were analysed by a narrative synthesis approach. Participants and setting: Structured interviews were held with 18 former caregivers of deceased patients with motor neuron disease. A total of 10 patients had created a disease-specific advanced directive, 'Letter of Future Care', and 8 had not. Results: A total of four global themes emerged: Readiness for death, Empowerment, Connections and Clarifying decisions and choices . Many felt the letter of future care was or would be beneficial, engendering autonomy and respect for patients, easing difficult decision-making and enhancing communication within families. However, individuals' 'readiness' to accept encroaching death would influence uptake. Appropriate timing to commence advance care planning may depend on case-based clinical and personal characteristics. Conclusion: Advance care planning can assist patients to achieve a sense of control and 'peace of mind' and facilitates important family discussion. However, the timing and style of its introduction needs to be approached sensitively. Tools and strategies for increasing the efficacy of advance care planning for motor neuron disease should be evaluated and implemented.